Sumbangan Paul Ricoeur dalam Proses Berteologi - John Christian Simon (Faculty of Theology Duta Wacana Christian University, 2018)
AbstractIn understanding the theologizing process, the foci are not only on the reality, but also on the means or tools to understand the reality. This article intends to explain the means or tools of theologizing process according to Paul Ricoeur. As a process what at stake is not only the method, but also the methodology, namely the thinking process, the interest of the subject and the premises on certain values. The guiding question is what is Ricoeur’s theologizing methodology, i.e. his hermeneutics? Through dialogue with many parties, Ricoeur found the methodology of reading reality is started with an affirmation and ended with a critic toward the distortion of reality; this is an affirmative-critical position. However, this methodology is inadequate to comprehend an extremely distorted reality. Hence, the present article offers a reversal move of theologizing process, by prioritizing the critical position toward the distorted reality and following up with the affirmation process by uncovering the element of hope of a good and just life. Ultimately, the theologizing process requires a dialectical methodology of reading the reality, between the critical-affirmative and affirmative-critical positions. The priority of the option is determined by the contextual challenges at hand. AbstrakDalam mengerti proses berteologi, perhatian kita tidak hanya tertuju pada realitas, melainkan juga pada sarana atau alat untuk memahami realitas. Tulisan ini bermaksud menjelaskan alat atau sarana dalam proses berteologi menurut Paul Ricoeur untuk digunakan memahami realitas. Sebagai sebuah proses, maka yang mau disentuh tidak hanya soal metode, melainkan metodologi, yaitu proses berpikir, kepentingan yang diusung, dan premis nilai yang dicapai. Pertanyaan yang dijadikan panduan adalah apa metodologi berteologi Ricoeur, yang sering disebut hermeneutik. Melalui dialog dengan banyak mitra, Ricoeur mendapati metodologi membaca realitas dengan pertama-tama bersikap afi rmatif baru kemudian kritis terhadap distorsi. Inilah gestur afi rmatif-kritis. Namun, metodologi ini tidak memadai untuk membaca konteks yang sudah demikian parah. Dibutuhkan upaya membalik prinsip metodologi Ricoeur dengan pertama-tama mengedepankan upaya kritis terhadap distorsi atas realitas baru kemudian afi rmatif untuk menguak pengharapan akan hidup yang baik dan adil. Pada akhirnya, proses berteologi membutuhkan metodologi membaca realitas secara dialektis, antara gestur kritis-afirmatif dan afirmatif-kritis. Mana yang dikedepankan sangat ditentukan oleh tantangan konteks yang dihadapi.